Reconstruction with a partial flap of the pectoralis major muscle, after complication of osteosynthesis of clavicle fracture - Fabiane Pinheiro; Fabricio Luis Pinheiro; Diego Loureiro Dos Santos; Claudio Messias Moraes; Ricardo Portella Perrone; Leandro Tuzuki Cavalheiro (Revista Brasileira de Cirurgia Plástica, 2021)
Introduction: The pectoralis major is a muscle that covers the upper portion of the anterior chest wall and is the first option for reconstruction of the chest wall and aesthetic purposes. Case Report: Male patient, 20 years old, presenting dehiscence of surgical wound, recurrent for three consecutive times, with exposure of the left clavicle osteosynthesis plate. Reconstruction was performed with the pectoralis major muscle to cover the plaque. Conclusion: This flap showed to be an excellent option for covering synthetic material exposure after multiple dehiscences of surgical wounds. The reconstruction was effective, with no complications and a satisfactory aesthetic result.